A Global Search Engine For Geospatial Data. - Upson, S. (IEEE spectrum)
Global Earth Observation System of Systems (GEOSS), a system architects which is essentially a search engine for environmental data, including not just data from Earth-observing satellites but also terrestrial sensor data, population figures, and regional health and ecosystem information. Formatting and indexing the data, designing a portal, and creating a standards repository are the fundamental, if humdrum, components upon which hinge the lofty goals of GEOSS: to improve environmental models and forecasting. The geographical coordinates for observations made on a moving platform are inherently less precise. Add to that the fact that many measurements are inferred from other properties for instance − temperature data come from infrared readings − and it's easy to see why space data are considered less reliable until they have been validated by overlapping observations made on Earth. Data from ground-based sensors, for their part, are less likely to be well indexed or touse standardized representations such as those based on XML, the mark-up language commonly used on the Internet. That makes it harder for researchers to locate and use the data. If all relevant sources of Earth-based information could be logically connected and recorded in well-documented formats, life would be a lot easier for modelers. Another goal of GEOSS architects is to persuade national governments to make more data freely available.